Ethanol and Glycerol Chemistry (IntechOpen, 2024)
Due to their unique physicochemical properties, low cost, and wide availability, ethanol and glycerol have gained attention for their use as alternative feedstocks in the sustainable production of several commodity and specialty products. As a result, during the last decades, there has been intense research aimed at developing the potential applications of these biomass-derived compounds. Ethanol and Glycerol Chemistry - Production, Modelling, Applications, and Technological Aspects discusses recent advances and different aspects of the production, direct applications, and processing of ethanol and glycerol from a multidisciplinary perspective that includes the medical field, fuels, and chemical synthesis.